The Amphimedon queenslandica genome and the evolution of animal complexity - Srivastava, Mansi; Simakov, Oleg; Chapman, Jarrod; Fahey, Bryony; Gauthier, Marie E. A.; Mitros, Therese; Richards, Gemma S.; Conaco, Cecilia; Dacre, Michael; Hellsten, Uffe; Larroux, Claire; Putnam, Nicholas H.; et al. (Nature, 2010)
Sponges are an ancient group of animals that diverged from other metazoans over 600 million years ago. Here we present the draft genome sequence of Amphimedon queenslandica, a demosponge from the Great Barrier Reef, and show that it is remarkably similar to other animal genomes in content, structure and organization. Comparative analysis enabled by the sequencing of the sponge genome reveals genomic events linked to the origin and early evolution of animals, including the appearance, expansion and diversification of pan-metazoan transcription factor, signalling pathway and structural genes. This diverse ‘toolkit’ of genes correlates with critical aspects of all metazoan body plans, and comprises cell cycle control and growth, development, somatic- and germ-cell specification, cell adhesion, innate immunity and allorecognition. Notably, many of the genes associated with the emergence of animals are also implicated in cancer, which arises from defects in basic processes associated with metazoan multicellularity.
Gesehen am 11.10.2023